The cicada genus Procollina Metcalf, 1952 (Hemiptera: Cicadidae): redescription including fourteen new species, with a key to the species of the subtribe Dazina Kato, 1932 rev. stat., the description of the Aragualnini n. tribe, and one new combination - Sanborn, Allen F. (Zootaxa, 2018)
The cicada genus Procollina Metcalf, 1952 is redescribed. Procollina minima n. sp., P. parva n. sp., P. ustulata n. sp. and P. webbi n. sp. are described from Costa Rica, P. guatemalensis n. sp., P. mayaensis n. sp. and P. nigrapilosa n. sp. are described from Guatemala, P. hondurensis n. sp. is described from Honduras, P. convexa n. sp. and P. mesomaculata n. sp. are described from Guatemala and Honduras, P. ulnamaculata n. sp. is described from Guatemala and Mexico, P. nuevoleonensis n. sp. and P. tamaulipasensis n. sp. are described from Mexico, and P. nicaraguaensis n. sp. is described from Nicaragua. The current eighteen species of Procollina are listed along with their synonymies and known distribution of each species. The tribe Dazini Kato, 1932 is moved from the Cicadettinae Buckton, 1889 to the Cicadinae Latreille, 1802, synonymized with the Zammarini Distant, 1905, and revised to the subtribe Dazina rev. stat. based on the morphological characters of the representative genera. A key to the species of the Dazina rev. stat. is provided. Aragualnini n. tribe is erected for the genus Aragualna Champanhet, Boulard & Gaiani, 2000 as it exhibits morphological characteristics of the Cicadettinae Buckton, 1889 rather than the Cicadinae as do the rest of the genera previously assigned to the Dazini. Finally, Cicada pennata (Distant, 1881) is reassigned to Neocicada Kato, 1932 to become Neocicada pennata (Distant, 1881) n. comb..